2022
DOI: 10.1155/2022/5388944
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Zinc Administration Combined with Swimming Exercise Prevents Cognitive-Emotional Disturbances and Tissue Injury following a Transient Hypoxic-Ischemic Insult in the Rat

Abstract: Exercise performance and zinc administration individually yield a protective effect on various neurodegenerative models, including ischemic brain injury. Therefore, this work was aimed at evaluating the combined effect of subacute prophylactic zinc administration and swimming exercise in a transient cerebral ischemia model. The prophylactic zinc administration (2.5 mg/kg of body weight) was provided every 24 h for four days before a 30 min common carotid artery occlusion (CCAO), and 24 h after reperfusion, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 122 publications
0
1
0
Order By: Relevance
“…Furthermore, a transgenerational study selecting for low capacity and high-capacity runners found male low-capacity runners had more severe ICH-induced brain injury and greater numbers of major histocompatibility complex class 2 1a (OX-6) positive microglia cells, demonstrating transgenerational regulation of microglia phenotype in a stroke model ( He et al, 2013 ). Both treadmill and swimming exercise have been found to regulate microglial numbers in different brain regions, such as the hypothalamus, hippocampus, basal ganglia, as well as in peri-infarcted and peri-hematoma zones ( Kinoshita et al, 2021 ; Xia et al, 2021 ; Aguilar-Peralta et al, 2022 ; Li et al, 2022 ). However, a single study by Svensson et al reported no impact of exercise on hippocampal microglial number or phenotype in a cerebral ischemic stroke model ( Svensson et al, 2016 ).…”
Section: Physical Exercise Regulates Microglia Function In Stroke Modelsmentioning
confidence: 99%
“…Furthermore, a transgenerational study selecting for low capacity and high-capacity runners found male low-capacity runners had more severe ICH-induced brain injury and greater numbers of major histocompatibility complex class 2 1a (OX-6) positive microglia cells, demonstrating transgenerational regulation of microglia phenotype in a stroke model ( He et al, 2013 ). Both treadmill and swimming exercise have been found to regulate microglial numbers in different brain regions, such as the hypothalamus, hippocampus, basal ganglia, as well as in peri-infarcted and peri-hematoma zones ( Kinoshita et al, 2021 ; Xia et al, 2021 ; Aguilar-Peralta et al, 2022 ; Li et al, 2022 ). However, a single study by Svensson et al reported no impact of exercise on hippocampal microglial number or phenotype in a cerebral ischemic stroke model ( Svensson et al, 2016 ).…”
Section: Physical Exercise Regulates Microglia Function In Stroke Modelsmentioning
confidence: 99%
“…The amygdala and hippocampus have the highest concentration of zinc while the brain's extracellular fluid has the lowest concentration [24][25][26]. The neuroprotective effects of zinc have also been reported severally [27][28][29][30]. While there have been reports of the ameliorative potential of zinc in methotrexate induced intestinal damage [31,32].…”
Section: Introductionmentioning
confidence: 99%